Juvenile dermatomyositis in an eleven-year-old boy: a case report and review of literature - Nasrin, Tanjina; Khondker, Lubna; Hassan, Mohammad Anwarul; Samaresh Chandra Hazra; Nahid, Afsana; Hassan, Muhammed Kamrul; Jahan, Sharmin (International Journal of Research in Medical Sciences, 2025)
Juvenile dermatomyositis (JDM) is a rare chronic autoimmune inflammatory condition characterized by systemic capillary vasculopathy and idiopathic inflammatory myopathy (IIM) that primarily affects the skin and musculoskeletal system, resulting in a characteristic rash and symmetric muscle weakness of the upper and lower proximal muscles, increased levels of serum muscle enzymes and myopathic electromyography. Dysphagia, respiratory problems, and aspiration pneumonia can occur due to the involvement of respiratory and oropharyngeal muscles in severe cases. Both immune dysfunction and environmental factors are thought to contribute to etiopathogenesis. It could be linked to genetics, an immune response to a virus, an adverse drug reaction, exposure to sunlight or internal malignancy. JDM is characterized by two periods of peak occurrence: one during infancy which is called juvenile DM (JDM), typically between the ages of 5 and 15, and another during maturity, typically between the ages of 40 and 60. Histologically, it is characterized by the presence of lymphocytic vascular inflammation and endothelial swelling. Management of JDM is complex and warrants a multidisciplinary approach including physiotherapists, dermatologists, specialist nurses and pediatric rheumatologists, with other specialists like cardiologist/pulmonologist. The long-term complications of JDM include prolonged and severe muscle weakness with muscle atrophy, cutaneous calcifications, scarring or atrophy, and lipodystrophy. Calcinosis cutis, a form of dystrophic calcification, is a late sequel of the disease and occurs in up to 40% of patients with this disorder, a major cause of morbidity. JDM has poor prognosis with one third of patients recovering without complication, one third develop disability and one third die. Herein, we reported a case of an 11-year-old boy who presented to us with facial puffiness & weakness in both limbs, classic clinical and histopathological features of Juvenile dermatomyositis (JDM). As early diagnosis and timely aggressive treatment are associated with better outcomes.